Comparison of Tiktok Application Users Between the Implementation of Creativity and Addictive Behavior - Risalah, Aisyah Mujahidah; Rina, Nofha (Green Publisher Indonesia, 2024)
TikTok application users have now reached all levels of society, especially teenagers who use the TikTok application as a medium to express themselves. Teenagers who access TikTok are considered to have the opportunity to use creative abilities in creating content on TikTok, but the Tiktok application, in fact, will also have a bad impact on individuals, especially teenagers who are still very unstable. Tiktok can have a negative impact where it makes its users more and more addicted every day. This study aims to understand and analyze the implementation of creativity and addictive behavior of TikTok users. Implementation using Torrance Test of Creative Thinking (TTCT) and addictive behavior using Bergen Social Media Addiction Scale. There are four aspects of creativity, namely fluency, flexibility, elaboration, and originality. While addictive behavior there are aspects of importance, tolerance, mood swings, withdrawal and relapse. The method used is quantitative descriptive, to find out more between creativity and addiction that TikTok users use. Based on the findings, 85% were able to implement their creativity on the TikTok application with the biggest aspect lying in the flexibility in utilizing the ability to identify problems or provide solutions to their problems by utilizing the features and visualizations available on TikTok. As for addictive behavior, it was found that 75% of addictive behavior existed, with the largest dimension in mood swings, this is because TikTokers are looking for fun and entertainment to forget for a moment about the problem.